Economic and Health Care Burdens of Hepatitis Delta: A Study of Commercially Insured Adults in the United States. Issue 2 (20th May 2020) - Elsaid, Mohamed I.; Li, You; John, Tina; Narayanan, Navaneeth; Catalano, Carolyn; Rustgi, Vinod K.
Abstract : Background and Aims: The paucity of data regarding the extent of hepatitis delta virus (HDV) associated health care burden in the United States is an important obstacle to assessing the cost‐effectiveness of potential intervention strategies. In this study, we characterized the health care use and cost burdens of HDV in the United States using real‐world claims data. Approach and Results: We conducted a case‐control study using the Truven Health MarketScan Commercial Claims databases from 2011‐2014. A total of 2, 727 HDV cases were matched 1:1 by sociodemographic characteristics and comorbidities to chronic hepatitis B virus (HBV) controls using propensity scores. The HDV group had significantly higher prevalence of substance abuse, sexually transmitted diseases, decompensated cirrhosis, cirrhosis, and hepatitis C virus compared to patients with chronic HBV. First HDV diagnosis was associated with significant increases in the total number of health care claims (25.61 vs. 28.99; P < 0.0001) and total annual health care costs (19, 476 vs. 23, 605; P < 0.0001) compared with pre‐HDV baseline. The case‐control analysis similarly indicated higher total claims (28.99 vs. 25.19; P < 0.0001) and health care costs (23, 605 vs. 18, 228; P < 0.0001) in HDV compared with HBV alone. Compared with HBV controls, HDV cases had an adjusted incident rate ratio of 1.16 (95% confidence interval: 1.10, 1.22) times the total number of annual claims and an adjusted incident rate ratio 1.32 (95% confidence interval 1.17, 1.48) times the total annual health care cost. Conclusions: HDV is associated with higher health care use and cost burden than HBV alone, underscoring the need for improved screening and treatment.